MUSIK MOZART MEMILIKI EKSPRESI SYNAPSIN 1 TERTINGGI PADA CEREBRUM DAN CEREBELLUM RATTUS NORVEGICUS BARU LAHIR DIBANDINGKAN DENGAN GAMELAN JAWA, SUNDA DAN BALI SELAMA KEHAMILAN - Yaner, Nurul Ramadhani; Joewono, Hermanto Tri; Widjiati, Widjiati (Universitas Tribhuwana Tunggadewi, 2021)
Stimulation classical music has been shown to influence the increase in brain function and the development of child intelligence. Mozart's classical music has a frequency that can stimulate the growth of synaptic tissue. This research was analyze differences in the expression of synapsin 1 cerebrum and cerebellum Rattus norvegicus was born from mothers exposed to Mozart music, traditional Javanese gamelan music, Sundanese, Balinese and who were not exposed to music during pregnancy. This research was using methods experimental with post test only control group design. The treatment was given to Rattus norvegicus animals from pregnancy day to 10-19, for 1 hour in a soundproof room, intensity of 65 dB. On the 20th day of pregnancy, Rattus norvegicus was sacrificed and 3 of the heaviest, medium and lowest Rattus norvegicus children were selected and the heads of Rattus norvegicus children were decapitated and brain dissection and synapsin 1 expression was calculated using an immunohistochemical method and analyzed with appropriate statistics. Result There were significant differences in the expression of newborn synapsin 1 Rattus norvegicus cerebrum between groups with a value of p = 0.042 (mean in the control group IRS: 2.04 ± 0.26, in the Mozart group IRS: 3.84 ± 1.66, Javanese gamelan group IRS: 2.64 ± 0.51, Sundanese gamelan group IRS: 2.92 ± 0.41, and in the Balinese gamelan group IRS: 2.52 ± 1.18) and so in the cerebellum with a value of p = 0.001 (mean in the control group IRS: 2.02 ± 0.30, in the Mozart group IRS: 4.72 ± 0.54, the Javanese gamelan group was IRS: 3.20 ± 0.82, the Sundanese gamelan group was IRS: 3.12 ± 0.83, and in the Bali gamelan group IRS: 2.08 ± 0.30). Conclusion There are differences in the expression of synapsin 1 of the Rattus norvegicus offspring exposed to Mozart music, gamelan traditional music Javanese, Sundanese and Balinese in the cerebellum but there are no differences in the cerebrum during pregnancy. The highest synapsin expression was in the Mozart group.